The Concept of Mercy: in Tafsir Fî Zhilâl Al-Qur'an - Nasyirudin Nasyirudin; Muhammad Mukharom Ridho; Murdianto Murdianto (Al-Munir: Jurnal Studi Ilmu Al-Qur'an dan Tafsir, 2026)
The concept of rahmah in the Qur’an is a term rich in meaning and highly contextual. In Tafsir Fî Zhilâl al-Qur’an, Sayyid Quthb presents rahmah as a form of divine mercy and grace that encompasses all creation, yet is specifically bestowed upon those who believe, migrate, strive in God’s path, remain patient, and practice excellence (ihsan). This study adopts a qualitative approach through library research focused on verses containing the term rahmah. The analysis reveals that rahmah, as interpreted in this tafsir, encompasses spiritual, social, and existential dimensions, and serves as a key motivation for drawing closer to God through righteous deeds and sincere faith. Abstrak Lafadz rahmat dalam Al-Qur’an merupakan istilah yang sarat makna dan kontekstual. Dalam Tafsir Fî Zhilâl al-Qur’an, Sayyid Quthb menguraikan rahmat sebagai bentuk kasih sayang dan anugerah Allah yang mencakup seluruh makhluk, namun secara khusus diberikan kepada hamba yang beriman, berhijrah, berjihad, bersabar, dan berbuat ihsan. Kajian ini menggunakan pendekatan kualitatif dengan metode studi pustaka terhadap ayat-ayat yang mengandung lafaz rahmat. Hasil analisis menunjukkan bahwa rahmat dalam tafsir ini mencakup dimensi spiritual, sosial, dan eksistensial, serta menjadi pendorong utama untuk meraih kedekatan dengan Allah melalui amal saleh dan kesungguhan iman.